Comparison of The Outcome of Transurethral Resection of Prostate with and Without Preoperative Finasteride (Bangladesh Journal of Urology, 2026)
Background: Transurethral Resection of Prostate (TURP) remains gold standard treatment option for BEP. But this procedure has got some expected complications, among them intra-operative and postoperative hematuria has a higher prevalence rate of 3.5-15.7 ℅. So effective strategies and measures should be adopted to ensure better postoperative outcome in TURP patients in terms of reducing peroperative bleeding and its related catastrophes. Short term pre-treatment with finasteride can be an option suited best for TURP in reducing per-operative blood loss & for better postoperative outcome. Methods: This was a hospital based quasi-experimental study conducted in the Department of Urology, Dhaka Medical College hospital, Dhaka in between   January, 2021 to December, 2021 with100 patients having enlarged prostate with moderate to severe LUTS aged within 50-80 years & with pre-operative prostate volume between 40-80 grams. The total sample size was divided in two groups. Whereby group A (n=50) had received 2 weeks of finasteride 5 mg once daily tablet and group B (n=50) was treated with vitamin-D3 2000 IU daily dose as a placebo prior to TURP. All of them underwent Trans-urethral Resection of Prostate. Post-operative follow up was designed as early post-operative follow up and follow up after 28 days of TURP.Results: The baseline variables were comparable among the groups. Statistically significant differences were seen in the time duration of resection which was respectively 43.97±8.79 min and 66.32±18.64 min (p value